Clavibacter michiganensis subsp. michiganensis strains from central Chile exhibit low genetic diversity and sequence types match strains in other parts of the world. (16th July 2018) - Valenzuela, M.; Besoain, X.; Durand, K.; Cesbron, S.; Fuentes, S.; Claverías, F.; Jacques, M. A.; Seeger, M.
Abstract : Bacterial canker caused by Clavibacter michiganensis subsp. michiganensis (Cmm) is one of the most important bacterial diseases of tomato. In order to understand the emergence and dissemination of this pathogen in Chile, Chilean Cmm strains isolated from different sites in central Chile were characterized and compared to a worldwide collection of strains. Multilocus sequence analysis and typing (MLSA‐MLST) based on five housekeeping genes, i.e. atpD, dnaK, gyrB, ppk and recA, and multilocus variable number of tandem repeats (VNTR) analysis (MLVA) based on eight VNTRs were used. Low diversity was found using MLSA‐MLST among the 25 Chilean strains, which clustered into three groups, each corresponding to a single sequence type (ST). Group I contained most strains (21/25), isolated over different years from Valparaíso and O'Higgins regions. Group II contained only one strain from Maule region that was isolated in 2005. These two groups belonged to the same genetic lineage. Group III contained three strains from Valparaíso region isolated in 2004, 2012 and 2013. MLVA also distributed the strains into the same three groups. Group III strains shared the same ST as strains from Algeria, Belgium, France, the Netherlands, Uruguay and the USA. Group II strains shared the same ST as strains from Brazil and Uruguay, while Group I strains shared the same ST as two strains of unknown origin. This study shows that Cmm strains from central Chile tend to be clonal and have similar genetic profiles to strains from other countries.